2019
DOI: 10.3892/mmr.2019.10701
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA NR_002794 is upregulated in pre‑eclampsia and regulates the proliferation, apoptosis and invasion of trophoblast cells

Abstract: Pre-eclampsia is a common complication during pregnancy, characterized by hypertension and proteinuria. The pathogenesis of pre-eclampsia is not fully understood. Studies on the maternal spiral artery have led scientists to consider that the ineffective infiltration of placental trophoblast cells may be a primary cause of pre-eclampsia. The present study aimed to investigate the differences in the profiles of long non-coding RNAs (lncRNAs) between the placentas of patients with pre-eclampsia and those of healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“… [ 171 ] NR_002794 placenta upregulated / NR_002794 has suppressive effects on proliferation and migration, and results in an increased rate of apoptosis. [ 172 ] MVIH placenta downregulated Jun-B The silencing of MVIH expression inhibits cell growth, migration, invasion, and angiogenesis in various trophoblast cell lines by modulating Jun-B protein expression. [ 173 ] GASAL1 placenta downregulated SRSF1/mTOR/EBP1/Bcl-2/caspase-3 lncRNA GASAL1 interacts with SRSF1 to regulate the proliferative, invasive, and apoptotic abilities of trophoblast cells via the mTOR signaling pathway.…”
Section: Lncrnas and Pementioning
confidence: 99%
“… [ 171 ] NR_002794 placenta upregulated / NR_002794 has suppressive effects on proliferation and migration, and results in an increased rate of apoptosis. [ 172 ] MVIH placenta downregulated Jun-B The silencing of MVIH expression inhibits cell growth, migration, invasion, and angiogenesis in various trophoblast cell lines by modulating Jun-B protein expression. [ 173 ] GASAL1 placenta downregulated SRSF1/mTOR/EBP1/Bcl-2/caspase-3 lncRNA GASAL1 interacts with SRSF1 to regulate the proliferative, invasive, and apoptotic abilities of trophoblast cells via the mTOR signaling pathway.…”
Section: Lncrnas and Pementioning
confidence: 99%
“…Deficiency of invaded trophoblastic cells is the one of main causes of dysfunctional placentas. Inadequate motility of trophoblastic cells leads to abnormal remodeling of spiral arteries and disrupts material exchange between fetus and mother, thus causing a series of pregnancy-related disorders [31,32]. Earlier study has revealed that trophoblast migration and invasion are correlated with the enhanced ability of dNK cells to produce IL-8 and IP-10, which bind to C-X-C motif chemokine receptor 1(CXCR1) and CXCR3 expressed by invasive EVT, respectively [33].…”
Section: Dnk Cells Regulate Trophoblast Invasionmentioning
confidence: 99%
“…Although PE has been extensively studied ( 11 ), the underlying pathogenesis of PE remains elusive. However, it is hypothesized that inadequate trophoblastic invasion may cause PE ( 12 , 13 ). Wu et al ( 14 ) reported that HIF1A-AS2 expression was significantly downregulated in the tissues of 52 patients with PE compared with the adjacent normal samples.…”
Section: Expression and Function Of Lncrna Hif1a-as2 In Several Types Of Cancermentioning
confidence: 99%